What can we learn from pupils’ dialogues? Second graders’ learning about division - A S Maulida; D Dasari; E Mulyana (Pascasarjana Universitas Pendidikan Indonesia, 2018)
Setting up lesson to introduce the concept of division by didactical situation for second graders’ student in one of private primary school in Bandung (March 2017). We set the lesson with the theme of ‘Let’s help Mrs Emma’. The lesson design was sharing four packs of chocolate for 5 persons. The situation, Mrs Emma got packages from her friends. The packs contain four packs of chocolate. The chocolates should be share for her family’s member, such as father, Mrs Emma, little sister, little brother, and grandma. Then, Mrs Emma asked pupils to work in group and discuss about how to share the chocolates. The analysis was focus on group discussion, about phenomenology in the classroom then identifying pupils’ ethical orientations and decisions when dividing chocolates. We know that each pupils had their own tacit knowledge. It means that through this lesson design, pupils making dialogues for negotiating their argument to solve this problem. Moreover, pupils learned about collaborating and respecting each other’s tacit.